2014
DOI: 10.1007/s40097-014-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

New superatom in alkali-metal atoms

Abstract: On the basis of a similarity with electronic states in alkali-metal atoms, the existence of a new artificial atom (superatom) has been predicted theoretically. This superatom may be considered as a new alkali-metal atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…1) [1][2][3][4][5][6]. The idea of a superatom (or artificial atom) was fruitful for the development of nanophysics [22,23]. A superatom (quasiatomic nanoheterostructures) consists of a spherical QD with radius a, the volume of which contains a semiconductor (or dielectric) material.…”
Section: Introductionmentioning
confidence: 99%
“…1) [1][2][3][4][5][6]. The idea of a superatom (or artificial atom) was fruitful for the development of nanophysics [22,23]. A superatom (quasiatomic nanoheterostructures) consists of a spherical QD with radius a, the volume of which contains a semiconductor (or dielectric) material.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have shown that with the rise of the exciton binding energy value in low-dimensional semiconductor systems, the biexciton binding energy value with growth confinement is also raised [25,[57][58][59][60][61][62][63][64][65][66][67]. All of the papers in this field have shown that by improving the biexciton creation in reduced dimensional semiconductor structures, the quantum yield (QY) of photovoltaic cells has been enhanced [57,[68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%